Interference reduction by null-forming optimization based MVDR technique using gravitational search algorithm - Shahab, Suhail Najm; Ayib Rosdi, Zainun; Alabdraba, Waleed M. Sh.; Nurul Hazlina, Noordin (EAI, 2017)
Interference reduction one of the major problem in the wireless communication systems. Minimum Variance Distortionless Response (MVDR) Beamformer is the process of extracting the user-of-interest (UOI) signal from interferer signals and external noise. In the present work, Gravitational Search Algorithm (GSA) is a new modern metaheuristic optimization technique used for optimizing the MVDR null-forming level by controlling the excitation weight coefficients in a linear antenna array radiation pattern synthesis. The best set of complex excitation coefficients solution in multidimensional problems evaluated based on two figure of merit, signal-to-interference-plus-noise ratio (SINR) and beam pattern accuracy for two scan angles. The results reported here have been compared with the results of conventional MVDR technique. MVDRGSA successfully used to calculate the excitation weight coefficients with the desired patterns for both accurate beam shaping and introduce deep pattern nulling. It found that the SINR and output beampattern were in good agreement with MVDRGSA.